OCT-1 is over-expressed in intestinal metaplasia and intestinal gastric carcinomas and binds to, but does not transactivate, CDX2 in gastric cells - Raquel Almeida (2005)
Intestinal metaplasia (IM) is a preneoplastic lesion of the stomach in which there is transdifferentiation of the gastric mucosa to an intestinal phenotype. The caudal-related homeobox gene CDX2 encodes an intestine-specific transcription factor crucial for the regulation of proliferation and differentiation of intestinal cells. In addition, CDX2 is involved in the induction of IM in the stomach. The aim of this study was to access the putative involvement of OCT-1 in the induction of CDX2 expression de novo in gastric mucosa leading to the onset of IM. OCT-1 protein expression was evaluated by immunohistochemistry in 31 biopsies with chronic gastritis, 15 biopsies with foci of IM and adjacent gastric mucosa and 42 gastric carcinomas. Furthermore, we evaluated OCT-1 binding by electrophoretic mobility shift assay and activation of the CDX2 promoter by co-transfecting a CDX2 promoter/reporter construct with an OCT-1 expression vector in two gastric carcinoma cell lines, GP220 and MKN45. Our results show that OCT-1 is expressed in chronic gastritis, particularly when it is adjacent to IM and is expressed in 87% of IM foci. Furthermore, 74% of the gastric carcinomas were positive for OCT-1 and a strong association was observed between OCT-1 expression and intestinal-type carcinoma. We identified that OCT-1 binds to the CDX2 promoter, although we could not see a transactivation effect in gastric carcinoma cell lines. In conclusion, we observed increased OCT-1 expression in IM and in intestinal gastric carcinomas and identified the capacity of OCT-1 to bind to the CDX2 promoter, although we could not demonstrate a direct effect of OCT-1 in the transactivation of CDX2. Copyright (c) 2005 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.